Phenomenon of Motion of Salt along the Walls of the Container (International Journal of Current Engineering and Technology, 2015)
In this article we report the phenomenon of motion of salt along the walls of the container containing the salt solution. When a table salt solution is left exposed to the atmosphere, the water naturally evaporates in several days. It is observed that as the water evaporates a thin layer of salt starts to form on the inner walls of the glass. This layer, from the inception, tends to form above the original level of the solution. Surprisingly, the layer spreads to the top of the glass and continues on to the outer wall of the glass. This surprising behaviour of the salt motion is described in detail along with the photographs.
Keywords: Salt Solution; Sodium Chloride; Motion of Salt